2018
DOI: 10.5152/tud.2018.19616
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes of tubed versus tubeless percutaneous nephrolithotomy in children: A single center study

Abstract: Objective: To evaluate and compare the effectiveness of tubeless percutaneous nephrolithotomy (PCNL) and tubed PCNL by using small bore nephrostomy tube (12Fr) in children for the management of nephrolithiasis. Material and methods:This study was a retrospective analysis of 35 children where tubed PCNL (Group 1) was done in 18, and tubeless PCNL (group 2) in 17 patients from January 2010 to December 2016. Charts were reviewed for age, mass, stone size, operative time, hospital stay and stone-free rates.These v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
4
7
0
2
Order By: Relevance
“…In our study, no difference was there in the longevity of hospital stay between the two groups. Similar findings were also reported in the study conducted by Iqbal et al [19]. In addition, the mean operative time in children is shorter than in adults.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, no difference was there in the longevity of hospital stay between the two groups. Similar findings were also reported in the study conducted by Iqbal et al [19]. In addition, the mean operative time in children is shorter than in adults.…”
Section: Discussionsupporting
confidence: 90%
“…For those authors, the mean operative time was 156±38.7 min for nephrolitholapaxia with a nephrostomy drainage and 160±41.1 min for the group without the nephrostomy. 40 Our mean operative time for nephrolitholapaxia is comparable to that of some of the referred authors -150±33.4 min. Our longer operative time is most likely due to our initial experience in performing the minimally invasive technique.…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, the success rate or complete stone removal in tubeless PCNL was signi cantly higher than standard PCNL which was consistent to the results of researches conducted by Aghamir et al 17 and the retrospective study by Bilen et al 18 . In the study by Iqbal et al 19 and the meta-analysis by Xun et al 20 and Nouralizadeh et al 21 no signi cant difference was observed between standard PCNL and tubeless considering the success rate.…”
Section: Discussionmentioning
confidence: 93%
“…Due to the results of researchers performed, kidney stone surgery in children and adults by tubeless PCNL method reduces the length of hospital stay after surgery 20,23 . In a study conducted by Mousavi Bahar et al in 2006, the average hospital stay was 48 hours 24 .…”
Section: Discussionmentioning
confidence: 99%